Sistem Penjualan dan Delivery pada Restoran Martabak Kubang dengan Metodologi Berorientasi Objek - Gilang Ryan Fernandes (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2018)
The sale and delivery of product at Martabak Kubang Restaurant still apply a manual system, leading to a less accurate sale and delivery process and to a time-consuming reporting process that make a decision-making difficult to do. The purpose of this research is to overcome the problems found in Martabak Kubang Restaurant by designing a sale and delivery system. The method used in this study is a qualitative approach by which the data on Martabak Kubang Restaurant are collected and researched to resolve the existing problems. The system is expected to assist in creating a fast, precise and accurate decision-making in order to solve complex problems and to facilitate the progress for Martabak Kubang Restaurant.